Perceptions of Student-Centered Learning in Teacher Training College in Laos - MOUACHONGTOUA, Nouaneinda (Souphanouvong University Journal Multidisciplinary Research and Development, 2025)
Today education is focusing on various teaching approaches, teachers should have familiarized with various effective approaches and ideal teaching method plans to bring order and productive learning back into the classroom activities. Increasing teachers’ quality is the major strategy of the education strategic plan to meet the education goal, Education Strategic Plan (2020-2025). Ministry of education must strengthen various methods in teaching to promote and adapt to the rapid changing educational environment. Therefore, the purpose of this study investigates science teacher trainers’ perceptions of student-centered learning in teacher training college in Laos and identify the challenges of practicing student- centered Learning during teaching activities. The study was conducted three teacher training colleges in Laos. The purposively selected approach was used to select teachers who teaching in Biology, Physic and Chemistry. One hundred science teacher trainers participated in this study. An online questionnaire was designed to collect data and distribute through an online survey platform, and post-interview was conducted further explain the quantitative findings in-depth. Descriptive statistics were applied to examine the teachers’ perceptions toward student- centered learning and the challenges them from practicing student- centered leaning in teaching activities. Findings indicated that teachers have favorable perception toward the practicing student-centered learning. Teachers were aware of the usefulness of student-centered leaning, and they are willing to use student-centered learning in their teaching activities. However, science teacher also facing with some challenges in their teaching with student-centered learning like heavy workload and lack of time. Some teachers were not confident in their competencies in using and teaching the student-centered approach efficiently and effectively. Therefore, teacher also perceived that using student-centered learning increased their workloads